Treated Soil by Cement to Produce Non-Fired Roof - Sadek Deboucha; Sidi Mohammed Aissa Mamoune; Ziani Hocine, (Algerian Journal of Research and Technology (AJRT), 2022)
In demand to minimize the environmental impacts produced by building materials, the opportunity of using cement stabilized soil tiles has been evaluated. Fired clay roofing tiles are one of the most widely used materials in Algerian constructions, whichare produced by firing methods with vast energy consumption and environmental pollution, which can be solved effectively by developing non-firing materials. In this study, non-fired tiles were prepared by mixing soil with different percentages of cement. Laboratory experiments including density, water absorption, porosity, compressive strength, flexural strength and linear shrinkage were conducted on stabilized soil tiles made with three contents of cement (5%, 10% and 15%).The strength values have exceeded the minimum standard requirement for roof tiles (800-1250 kPa) with low water absorption, porosity and lower shrinkage in most samples compared to fired clay tiles.The results obtained made it possible to conclude the possibility of producing non-fired tiles.